Blood red lines : how nativism fuels the Right - O'Connor, Brendan (Journalist) (Haymarket Books, 2021)
"Blood-Red Lines is a forensic deep-dive into the dark arterial network of the anti-immigrant far-right. In an engaging journalistic method and story-telling style, O'Connor presents a map-like, chronological exposé of the white nationalist origination of restrictionist policy and its comfortable convergence with capitalist political economy. He painstakingly details the methods by which these toxic ideas have enabled opportunists, demagogues, and fascist foot-soldiers to gain entry and influence within the political mainstream. Not to despair, O'Connor also introduces us to the people, organizations, and efforts taking shape to defeat the resurgent far-right. Anyone trying to understand how the far-right has surged in ranks and influence in recent decades--and everyone committed to the cause of justice for migrants and refugees--needs to read this book and take action."--Jacket flap.